2016
DOI: 10.1002/ecy.1529
|View full text |Cite
|
Sign up to set email alerts
|

Absence of net long‐term successional facilitation by alder in a boreal Alaska floodplain

Abstract: Long-term experiments provide a way to test presumed causes of successional or environmentally driven vegetation changes. Early-successional nitrogen (N)-fixing plants are widely thought to facilitate productivity and vegetation development on N-poor sites, thus accounting for observed vegetation patterns later in succession. We tested this facilitative impact on vegetation development in a 23-yr field experiment on an Interior Alaska (USA) floodplain. On three replicate early-successional silt bars, we plante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…The study sought to integrate abiotic controls and disturbance pressure with ecosystem conservation indicators to develop strategies in preserving biodiversity. In another study with SEM, a 23-year field experiment on a plant community in an Alaskan floodplain, found that alder inhibited spruce growth in the drier site directly, while at the wetter site it inhibited growth indirectly through effects mediated by competition with other vegetation and herbivory (Chapin et al 2016). …”
Section: Sem Basics Path Analysismentioning
confidence: 99%
“…The study sought to integrate abiotic controls and disturbance pressure with ecosystem conservation indicators to develop strategies in preserving biodiversity. In another study with SEM, a 23-year field experiment on a plant community in an Alaskan floodplain, found that alder inhibited spruce growth in the drier site directly, while at the wetter site it inhibited growth indirectly through effects mediated by competition with other vegetation and herbivory (Chapin et al 2016). …”
Section: Sem Basics Path Analysismentioning
confidence: 99%
“…In light of previous studies demonstrating the capacity for hares to significantly reduce spruce height in lowland floodplains [ 4 , 14 ], we investigated whether treeline spruce would also experience reduced height as a result of snowshoe hare herbivory. We addressed this question by measuring the height, age, and browsing history of white spruce seedlings at two treeline locations in Alaska: at the altitudinal limit of white spruce in Denali National Park, and at the latitudinal limit of the species near the Middle Fork of the Koyukuk River.…”
Section: Introductionmentioning
confidence: 99%
“…The CO 2 sequestration component of our model relies on the theory that N-fixing trees drive forest growth by meeting its N demand, which has some 3,4 but not universal 3133 support. For example, Batterman et al 3 found that in a 300-year forest chronosequence in Panama, N-fixing trees provided over 50% of the N demand of early successional forest growth.…”
Section: Discussionmentioning
confidence: 99%